Influence of responsiveness, flexibility, accuracy and professionalism on E-hailing service performance in the Klang Valley, Malaysia - Ramli, Muhammad Shahman Shahfiq (2020)
The purpose of this study is to examine the influence of responsiveness, flexibility, accuracy and professionalism on the E-hailing service performance in Klang Valley, Malaysia. Research on the E-hailing performance has mainly focused on the private sector compared to the public sector. It is because the private sector is more cautious than the public sector regarding the service provided. Thus, this gap has resulted in an unreliable, insufficiently transparent, and inefficient service of public sector organisations. Given the limited previous studies conducted in this field and the lack of transportation services available, the current study evaluated the E-hailing performance in Klang Valley, Malaysia. In Malaysia, particularly in the rural areas, E-hailing services are not able to provide access to the public view, thus preventing them from providing good transportation services. Residents in rural areas have raised serious concerns about the negative performance of public transport services and some of the private transport services due to poor service quality. Thus, this study suggests the development of a framework to create and enhance the performance of E-hailing services. In this study, the research framework was built upon the tenets of SERVQUAL, sociological theory and resilience theory. Data were collected from 391 respondents across Kuala Lumpur and the Klang Valley and then analysed using Partial Least Squares, Structural Equation Modelling (PLS-SEM). The results of these analyses confirmed that three of the proposed factors in service, namely (1) responsiveness, (2) flexibility, and (3) accuracy are significant predictors of E-hailing service performance. Other findings suggest that professionalism can be achieved through flexibility and accuracy. Professionalism was also observed to significantly mediate the relationships between flexibility, accuracy, and E-hailing service performance. Form a broader perspective, this study confirms how the different factors on professionalism can develop and enhance the performance of E-hailing services.